Synthesis and DNA-Binding of Transition Metal Complexes with 3,4- Dimethoxyphenylacetic Acid - Hang-Ming, Guo; Guo-Liang, Zhao; Xiao-Yong, Wu (Asian Journal of Chemistry, 2011)
Three complexes with the general composition [M(DMPA)2(H2O)2] 1-3 (HDMPA = 3,4- dimethoxyphenylacetic acid, C10H12O4; M = Ni, (1); Cu, (2); Zn, (3)) were synthesized from 3,4-dimethoxyphenylacetic acid and Ni(OH)2, Cu2(OH)2CO3, Zn(OH)2. All these complexes were characterized by elemental analysis, molar conductance, IR spectroscopy, thermal analysis. The DMPA– ligand behaves as a bidentate ligand having a O,O donor sets towards the metal cations. In all the three metal complexes, the central M(II) ion coordinates with both two DMPA– ligands via four oxygen atoms of carboxylato groups and two water molecule via their two oxygen atoms. The coordination numbers are tentatively assigned as six. The interaction between these metal complexes and DNA were studied by EtBr fluoescent probe.